Echocardiographic and electrocardiographic findings in patients with obesity hypoventilation syndrome. Issue 1 (January 2015) - Alawami, M.; Mustafa, A.; Whyte, K.; Alkhater, M.; Bhikoo, Z.; Pemberton, J.
Abstract Background Obesity is a risk factor for both sleep‐related breathing disorders (SRBD), including obesity hypoventilation syndrome (OHS) and cardiovascular diseases (CVD). The development of CVD in patients with SRBD is usually attributed to the fact that most patients are obese in addition to conventional cardiovascular risk factors. Aims This study aims to measure the prevalence of certain CVD in patients with OHS in the Auckland region and highlight the importance of the effects of SRBD on the heart. Methods A dataset of all patients with a formal diagnosis of OHS that were under active follow up was compiled from Auckland District Health Board Sleep Disordered Breathing Service. Clinical notes were retrospectively reviewed for echocardiogram reports, blood pressure measurements and electrocardiograms. Results Forty‐seven patients were included in the present study. The median age was 60 years, 24 were female (51%), 20 (42.5%) had diabetes, mean HbA1C was 53.5 mmol/mol, mean systolic blood pressure was 127 mmHg, mean body mass index was 49 kg/m2, mean forced expiratory volume in 1 s was 1.7 L, mean estimated glomerular filtration was 71 mL/min/1.73 m2 and there was anti‐hypertensive use in 31 (65.9%) patients. Thirty‐three patients had poor quality echocardiography views (70.2%). Left ventricular systolic and diastolic function was impaired in 8 (25%) and 18 (60%) respectively. Right ventricular dysfunction and pulmonary hypertension was present in 19 (63.3%) and 13 (52%) respectively. Sixteen patients (34%) had recurrent atrial or ventricular arrhythmias. Conclusion There appears to be a high prevalence of right ventricular impairment, pulmonary hypertension, left ventricle hypertrophy, diastolic dysfunction and arrhythmias in patients with OHS. These findings would appear to be higher than expected in obese patients without OHS. A larger prospective matched cohort study would be needed to confirm the clinical significance of these findings.